Time and sequence of eruption of primary teeth in relation to breastfeeding in sudanese children - Affan, Amal Abu; Eid, Enaam A. (Brazilian Dental Science, 2014)
Background: The eruption age at which the deciduous teeth start appearing in the oral cavity has been of great significance and interest to investigators and parents mainly due to its relation to the growth and development of the child. Objectives: To determine the mean eruption time and sequence of primary dentition among a sample of Sudanese children in Khartoum localities and to investigate the effect of gender and breastfeeding pattern on the timing and sequence of eruption. Materials and Methods: Random sample of 563 Sudanese children (283 boys and 280 girls) age 4-40 months were clinically examined and inspected for the eruption of primary teeth. The age of eruption of the teeth was estimated using Probit regression. Results: All the primary teeth erupted earlier in boys than in girls except the first primary molars. The first primary teeth to erupt were the mandibular central incisors at the mean age of 8.02 ± 3.28 months. No significant difference was found in the eruption time between right and left sides of jaws as well as between children with exclusive breastfeeding and non exclusive breastfeeding. Keywords: Eruption time; Primary teeth; Lower incisors; Deciduous molars.